الوعي بالاستدامة والاستعداد المؤسسي لمبادرة "نوى" في جامعة طرابلس (Al-Farooq Journal of Sciences, 2026)
Background: Universities are increasingly recognised as catalysts for sustainable development, yet there is limited empirical evidence on whether academic communities are cognitively and institutionally ready to engage in structured sustainability initiatives.Objective: This study investigates sustainability awareness, behavioural practices, and institutional readiness within the University of Tripoli to assess the strategic viability of the "Nawa" Initiative, a multi-pillar program integrating digital empowerment, leadership, mental health, environmental sustainability, water management, disability inclusion, and crisis management.Methods: A descriptive-analytical design was used, surveying 200 randomly selected participants (students, faculty, and staff) across multiple faculties. Data were collected via a structured questionnaire measuring awareness, practices, familiarity with Nawa’s pillars, and willingness to engage.Results: While individual sustainable behaviours are high (95.4% maintain cleanliness; 47.7% consistently rationalise resources), organised institutional participation is very low (64.4% rarely or never engage). Awareness of Nawa’s specific pillars remains weak (62–72% unfamiliar), indicating a conceptual gap, not resistance. Strikingly, 94.8% express willingness to participate if a structured framework exists.Conclusion: The University of Tripoli possesses latent human capital and ethical readiness for sustainability, but lacks an institutional mechanism to channel it. The Nawa Initiative is not only viable but necessary, transforming spontaneous prosocial behaviour into a coordinated, scalable model for university-led social responsibility. Our findings mandate the immediate adoption of Nawa as an institutional framework, including activation of student ambassadors, targeted awareness campaigns, and continuous impact assessment. These positions place the University of Tripoli as a regional benchmark for evidence-based sustainability initiatives.
Keywords: Sustainability Awareness; Institutional Readiness; Sustainable Development; Community Engagement; Youth Empowerment; Nawa Initiative